Study On The Road Transmitted Vibration Of A Mountain Bicycle - Ismail, Ahmad Yusuf; Mat Nuri @ Md Din, Nur Rashid; Ahmad Mansor, Mazlan; Shukri, Muhamad Farid Anwar; Afiq, Mohamad Amirul (Penerbit UTM Press, 2015)
-